Pre-performance routines, accuracy in athletic performanceand self-control - Perry, I. S.; Katz, Y. J. (Athens Journal of Sport, 2015)
The aim of this study is to define the relationship between Pre-Performance Routine (PPR), accuracy of athletic performance and self-control. The research sample consisted of 240 high school students randomly assigned one of three groups: a motor-cognitive preparedness group (MMPPR); a motor preparedness group (MPPR); and a control group who participated in six instructional sessions. The first and the second experimental groups were shown videos of how elite athletes prepare themselves for a golf putt, a tennis serve, a volleyball serve and a basketball free throw. Members of the control group were told to concentrate on the technique used in golf putts, tennis serves, volleyball serves and basketball free throws. Thereafter the participants performed golf putts, tennis serves, volleyball serves and basketball free throws and the accuracy of these actions were measured. In addition, the participants were required to respond to a self-control questionnaire before and after the intervention. Overall research findings concluded that members of the MMPPR group were more accurate in their athletic performance than members of the MPPR group who in turn attained a higher level of accuracy in their athletic performance than members of the control group.